Neuroendocrine Tumor of Larynx: A Case Report - Paudel, Deepak; Shrestha, Amod; Chettri, Shyam Thapa; Sah, Bajrang Prasad; Upadhyaya, Paricha (Journal of College of Medical Sciences-Nepal, 2020)
Neuroendocrine neoplasms of the larynx are rare but are the second most common tumors of the region. It is difficult disease to diagnose due to clinical and pathological heterogeneity of the condition. We report a 50 year old non-smoker lady with neuroendocrine tumor of supraglottic region of the larynx who was managed with endoscopic excision of the tumor and had no recurrence till 2 years of follow up.